ETMM-05. LACTIC ACID FACILITATES GLIOBLASTOMA GROWTH THROUGH MODULATION OF THE EPIGENOME. (25th March 2021) - Torrini, Consuelo; Nguyen, Trang; Shu, Chang; Mela, Angeliki; Humala, Nelson; Mahajan, Aayushi; Karpel-Massler, Georg; Bruce, Jeffrey; Canoll, Peter; Siegelin, Markus
Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor with an unfavorable prognosis. While GBMs utilize glucose, there are other carbon sources at their disposal. Lactate accumulates to a significant amount in the infiltrative margin of GBMs. In the current study, we demonstrated that lactate rescued patient-derived xenograft (PDX) GBM cells from nutrient deprivation mediated cell death and inhibition of growth. Transcriptome analysis, ATAC-seq and CHIP-seq. showed that lactic acid exposure entertained a signature of cell cycle progression and oxidative phosphorylation (OXPHOS) /tricarboxylic acid (TCA)-cycle. LC/MS analysis demonstrated that U-13C-Lactate elicited substantial labeling of TCA-cycle metabolites, acetyl-CoA and histone protein acetyl-residues in PDX derived GBM cells. Given that acetyl-CoA is pivotal for histone acetylation we observed a dose-dependent elevation of histone marks (e.g. H3K27ac), which was rescued by genetic and pharmacological inhibition of lactic acid-uptake, ATP-citrate lyase, p300 histone-acetyl-transferase and OXPHOS, resulting in reversal of lactate mediated protection from cell death. CHIP-seq. analysis demonstrated that lactic acid facilitated enhanced binding of H3K27ac to gene promoters and cis-regulatory elements. Consistently, ATAC-seq. analysis highlighted enhanced accessibility of the chromatin by lactic acid. In a combined tracer experiment (U-13C-glucose and 3-C13-lactate), we made the fundamental observation that lactic acid carbons were predominantly labeling the TCA cycle metabolites over glucose, implying a critical role of lactic acid in GBMs. Finally, pharmacological blockage of the TCA-cycle, using a clinically validated drug, extended overall survival in an orthotopic PDX model in mice without induction of toxicity, implying a critical role of lactic acid in GBMs and establishing lactic acid metabolism as a novel drug target for GBM.